Pengujian Akurasi kVp dan Linearitas pada Pesawat Sinar-X di Laboratorium Prodi Diploma III Teknik Radiodiagnostik dan Radioterapi Purwokerto - Asri Indah Aryani; Indra Kartika Nugroho; Panji Wibowo Nurcahyo (Jurnal Imejing Diagnostik (JImeD), 2016)
Background: Quality control is part of the quality assurance program related to the techniques used in the monitoring the maintenance of the technical elements of the system that affect picture quality. KVp accuracy and linearity (test mAs) is one of the components which are tested on the routine test performance evaluations. The X-ray Biomedical International unit brands BRG 100 RF of Laboratory Diploma in Mechanical Radiodiagnostic and Radiotherapy Purwokerto have not been tested yet. The objectives of this study are to determine suitability output kVp accuracy and linearity that have been beeing setting at control panel X-ray unit.Methods: This research belongs to a quantitative research which was conducted in April 2016 at the Laboratory of Radiodiagnostic Diploma Engineering and Radiotherapy Purwokerto on X-ray Biomedical International unit brands BRG 100 RF. The tests carried out two stages of testing. They were the accuracy of kVp with MPD (Multi-purpose detector) tool at kVp 50, 60, 70, 80, 9 and testing linearity method using Stepwedge and Reciprocity mAs Densitometer at 55 kVp, 10 mAs with a variation of 200 mA and 100. The results was analysed based on the quality control examining contained in KMK RI No.1250, the value of deviation accuracy of kVp 6% and for linearity deviation value (mAs) ≤ ± 0.1.Result: The test results showed that there are some deviations occur repeatedly on the accuracy of kVp on the value of eksposi 50, 60, 70, 80, 90, are 0.78%, 1.31%, 1.32%, 1.63%, 2.5%, but the deviation is still within the allowable limits that does not exceed 10%. The linearity testing showes that there are differences in optical density values on the radiograph with variations mA and s which are still within the allowable limit that is ≤ ± 0.1.Conclusion: Based on the result of kVp accuracy and linearity test, the deviation value is still within the tolerance limit or still in accordance with the permissible tolerance according to KMK RI   1250 about quality control testing parameter